2015
DOI: 10.2139/ssrn.2651907
|View full text |Cite
|
Sign up to set email alerts
|

Misconduct in Financial Services: Differences across Organizations

Abstract: We examine misconduct in Önancial services. We propose a theory in which experts extract surplus based on the value of their Örmís brand and their own skills. Using sales complaint data for insurance agents, we Önd that agents working exclusively for large branded Örms are more likely to be the subject of justiÖed sales complaints, relative to smaller independent experts, despite doing substantially less business. In addition, more experienced experts attract more complaints per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Unless all employees are cognizant of the existence of such policies and feel confident to exercise their right to appeal, these policies become ineffective and futile with the passage of time. Brown and Minor (2015) have discussed various malpractices among different organizations and state that financial misconduct at the workplace is a dishonorable act that leads an institution towards a diminished status and shameful notoriety. Broadly speaking financial frauds in universities may involve frauds by misuse of financial resources, false representation, failing to disclose information, and abuse of position.…”
Section: Considermentioning
confidence: 99%
“…Unless all employees are cognizant of the existence of such policies and feel confident to exercise their right to appeal, these policies become ineffective and futile with the passage of time. Brown and Minor (2015) have discussed various malpractices among different organizations and state that financial misconduct at the workplace is a dishonorable act that leads an institution towards a diminished status and shameful notoriety. Broadly speaking financial frauds in universities may involve frauds by misuse of financial resources, false representation, failing to disclose information, and abuse of position.…”
Section: Considermentioning
confidence: 99%
“…Yet, financial misconduct is not rare, even when there is a fiduciary duty towards investors. In financial markets fraud takes the form of dishonest schemes, promises of unrealistic returns, book cooking or favoritism (e.g., Cooper and Frank (2005); Mullainathan et al (2012); Piskorski et al (2015); Brown and Minor (2016); Pool et al (2016); Anagol et al (2017)). After building a large dataset of financial advisers in the United States from 2005 to 2015, Egan et al (2019) found that about seven percent of advisers have misconduct records, and this percentage goes up to 15 percent at some of the largest advisory companies.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational fraud and professional misconduct are relatively widespread in market societies (for recent examples in the financial sector, see Cohn et al, 2014;Piskorski et al, 2015;Brown and Minor, 2016;Egan et al, 2019). An aggressive market culture together with a rise of competition between and within organizations are frequently evoked to explain the erosion of moral norms in occupational settings.…”
Section: Introductionmentioning
confidence: 99%